Preparation and Characterization of an Amphipathic Magnetic Nanosphere - Yongsheng Ji; Ruihong Lv; Zhigang Xu; Chuande Zhao; Haixia Zhang (Journal of Analytical Methods in Chemistry)
The amphipathic magnetic nanospheres were synthesized using C8 and polyethylene glycol as ligands. Their morphology, structure, and composition were characterized by transmission electron microscope, Fourier transform infrared, and elementary analysis. The prepared materials presented uniform sphere with size distribution about 200 nm. The magnetic characteristics of magnetic nanomaterials were measured by vibrating sample magnetometer. The target products had a saturation magnetization value of 50 emu g−1 and superparamagnetism. The adsorption capability was also studied by static tests, and the material was applied to enrich benzenesulfonamide from calf serum. The results exhibited that the C8-PEG phase owned better adsorption capability, biocompatible property, and dispersivity in aqueous samples.